Breathless, a Drosophila FGF receptor homolog, is required for the onset of tracheal cell migration and tracheole formation. - Reichman-Fried, M.; Shilo, B.Z. (Mechanisms of Development, 1995)
Breathless, a Drosophila FGF receptor homolog (DFGF-R1), was shown to be essential for the migration of the tracheal cells and the posterior midline glia cells. The temporal requirement for the activity of this receptor was dissected by a dominant-negative construct lacking a functional cytoplasmic tyrosine-kinase domain. Induction of the construct prior to the onset of tracheal or glial cell migration produced phenotypes that were similar to those observed in the corresponding tissues of breathless null mutant embryos. However, this effect is not detected if the dominant-negative receptor is induced after the initiation of tracheal cell migration, indicating that Breathless is required primarily at the onset of the migration process. Induction of the construct after the tracheal branches are completed, blocked the formation of tracheoles, i.e. extension of cellular processes by the terminal tracheal cells, demonstrating that Breathless plays an essential role in this process as well. The requirement for Breathless at the onset of migration and the diversity of processes in which it participates, suggest that the receptor is involved in triggering transcription factors, which may be distinct for each context.